BICARA PROFESIONAL DI DUNIA KERJA: TEKNIK WAWANCARA DAN KOMUNIKASI CERDAS UNTUK SISWA LPK SAKURA - Irwan Nopian Sinaga; Evi Novalin Bako; Lapiti Gokmatua Sagala (Publikasi Kegiatan Pengabdian Masyarakat Widya (PUNDIMASWID), 2025)
The Sakura Education Community Service Program (LPK Sakura Education) plays a strategic role in producing a skilled, industry-ready workforce. To maximize students' technical potential, strengthening soft skills is essential, particularly in presenting their competencies during the job selection process. This Community Service Program (PKM) aims to strengthen students'job readiness through training in interview techniques and intelligent communication. The methods used included an explanation of professional communication theory, a strategic narrative development workshop using the STAR method, and a one-on-one interview role-play session. This activity was held on January 22, 2026, and was attended by 30 enthusiastic students. Evaluation results showed a 44% increase in the quality of their speech structure and a 43% increase in self-confidence. Through this training, students were able to align technical expertise with professional communication skills. This program successfully increased the marketability of LPK Sakura Education graduates, making them better prepared to compete in the global job market. Keywords: Human Resource Development, Interview Techniques, Job Readiness, LPK Sakura, Professional Communication.